Development of the elderly care model in community through a senior citizen school in Sang-thor Sub-district, Khueng-nai District, Ubon Ratchathani Province - Srisen, Numfon; Leethongdee, Songkramchai; Semrhum, Wirote (UBRU Journal for Public Health Research, 2020)
The purpose of this action research was to develop the Elderly Care Model in Community through A Senior Citizen School in Sang-thor Sub-district, Khueng-nai. There were the policy makers, the practitioners, and the elderly totally 84 people participated in this study. Quantitative data was collected by using the questionnaires developed by the researcher. Data was analyzed by using descriptive statistics: percentage, mean, and standard deviation, and using inference statistics: Wilcoxon matched-pairs signed rank test. Qualitative data was collected by using group discussion and was analyzed by using content analysis. This research found that developing of the Elderly Care Model for 8 steps, such as 1) Study the context of the community, appoint a working group.2) Selection of target groups for research.3) Analyze the problems.4) implementing plans.6) Follow up and support operations. 7) Evaluate. 8) Summarize the lesson learned. This time, causing a system of operations in the area development a new model “S T E S Model” (Sang-Thor Elderly School Model), Is a work process that is strengthened by the process. Furthermore, from this study the policy makers and the practitioners had more knowledge, more collaboration, and more satisfaction than before. The elderly also had more knowledge to improve self-care behaviors, less depression, ultimately improve quality of life. Therefore, the success factors consisted of 1) clear policy and procedure, 2) network and collaboration, and 3) the operation strength of the team.